Upper limb joint torques during performances of kicking pullovers - Konosu, A.; Yoshioka, S.; Fukashiro, S. (International Journal of Sport & Health Science, 2017)
In this study, we determined upper limb joint torques during performances of kicking pullover. Kinematics and bar reaction forces (BRFs) were measured during successful kicking pullovers by 10 healthy adult males, with the horizontal bar set at 75% to the individual subject`s heights. Sagittal plane analyses using an 11-segment link model were performed between the period from takeoff to the upside-down position. Large extension torques of elbows and shoulders of both arms were observed (1.01 ± 0.14 and 2.08 ± 0.30 Nm/kg as the sum of bilateral arms, respectively) and accompanied by large vertical BRF (0.71 ± 0.07 BW). Because the angular momentum about the center of mass (CM) was mostly satisfied at takeoff, large horizontal BRF after takeoff may be avoided. However, vertical velocity of the CM at takeoff (1.1 ± 0.1 m/s) was insufficient to raise by the necessary distance against gravity, and compensation by vertical BRF after takeoff was demonstrated. Moreover, vertical BRF was responsible for maintaining the position of the body at around the target height against gravity during the second half of the target period. These observations suggest that successful kicking pullovers require large elbow and shoulder extensor strengths, and strengthening of these muscles is effective for achieving kicking pullovers.